2011
DOI: 10.1111/j.1399-5448.2011.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the incidence of type 1 diabetes in Israeli children following the Second Lebanon War

Abstract: For the first time in a large population, we found a positive association between the trauma of war and an increase in the incidence of type 1 diabetes in children and adolescents. The increase in incidence was not associated with genetic susceptibility to the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
2
19
2
2
Order By: Relevance
“…Comparison with other studies Our prospective study confirms the findings from several retrospective studies that observed an association between type 1 diabetes and previous experiences of SLEs [7][8][9][10][11][12][13][14][15][16][17]. Some previous studies found an association with stressful life events in general [9,10,[14][15][16], while other studies were more limited to specific events [7,8,13,17], events judged as negative for the child [12] or specific events in a specific age group [11].…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 79%
See 4 more Smart Citations
“…Comparison with other studies Our prospective study confirms the findings from several retrospective studies that observed an association between type 1 diabetes and previous experiences of SLEs [7][8][9][10][11][12][13][14][15][16][17]. Some previous studies found an association with stressful life events in general [9,10,[14][15][16], while other studies were more limited to specific events [7,8,13,17], events judged as negative for the child [12] or specific events in a specific age group [11].…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 79%
“…Some previous studies found an association with stressful life events in general [9,10,[14][15][16], while other studies were more limited to specific events [7,8,13,17], events judged as negative for the child [12] or specific events in a specific age group [11]. However, previous retrospective studies have the methodological shortcoming of recall bias, which has been, for the first time on an individual level, avoided in the current study.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 40%
See 3 more Smart Citations